Analysis of the right to reply as case settlement in press release - Alfan Pathriansyah Masagala (Jurnal Hukum Volkgeist, 2020)
Freedom of the press is a reflection of a country that adheres to a democratic system. The freedom of the press is based on the 1945 Constitution Article 28. During the reform period through Minister Yunus Yosfiah the legalization of Law No. 40 of 1999 concerning the Press replaces Law No. 21 of 1982 amendment to Law No. 11 of 1966 concerning the Principal Provisions of the Press. The right of reply is a form of press freedom which is the settlement of a case if there is a problem in press reporting. Problem Formulation 1) How is the application of the Right to Answer as a case resolution in press reporting? 2) Why is the Right of Reply as the settlement of the case in press reporting less effective? The research method used is a normative juridical method. The conclusion of this study is that the Right to Answer has been set since Law No. 11 of 1966 concerning the provisions of the Press to Law No. 40 of 1999 concerning the Press, the Right of Reply in more detail is regulated in Press Council Regulation No. 9/regulation-DP/X/2008 concerning Guidelines for the Right to Reply. In reality the Right of Reply is not effective as a settlement of a case in a press release due to lack of regulatory substance in the Right of Reply. Right of reply is only seen as a settlement of cases in the realm of Ethics